Factors Influencing Job Change Desire: An Empirical Study on Employees in Startup Environments - Djaganata, Almirazada Dwiratu; Pusparini, Elok Savitri (Universitas Airlangga, 2024)
Objective: The study aimed to investigate and evaluate the impact of person-organization fit (POF), person-job fit (PJF), and person-group fit (PGF) on turnover intention through job satisfaction (JS) in startup companies. Startup companies play an important role in society and the global economy. Design/Methods/Approach: Data was gathered through an online survey of workers in startup businesses, with 449 data. The analytical method used in this study was LISREL's Structural Equation Modelling (SEM) analysis to examine the relationship between employee fit, such as person-organization fit, person-job fit, and person-group fit, on turnover intention, mediated by job satisfaction. Findings: The findings show that job satisfaction is positively and significantly impacted by person-organization fit, person-job fit, and person-group fit. Job satisfaction was found to fully mediate the effect of person-organization fit, person-job fit, and person-group fit on turnover intention. Originality: Limited research focuses on startup companies, so this study is unique. There is still a need for more research on person-group fit, as most research has focused on person-organization fit and person-job fit. Practical implication: In order to create and maintain job satisfaction among employees, companies can create an environment that encourages open and transparent communication within companies, letting employees freely express their thoughts, ideas, and concerns. Furthermore, prioritizing work-life balance by offering flexible work schedules is critical to increasing job satisfaction. Then, they should align with their values, provide rewards, provide effective supervision, and foster a positive work environment. This is crucial to reduce turnover intention in startup companies.